Hubungan Keikutsertaan Ibu Dalam Kelas Ibu Hamil Dengan Pengetahuan Mengenai Tanda Bahaya Kehamilan Dan Persalinan Di Wilayah Kota Denpasar - Ni Ketut Devy Kaspirayanthi; Ni Wayan Suarniti; Ni Ketut Somoyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2019)
Maternal Mortality Rate (MMR) in Indonesia is still high because the lower knowledge of pregnancy woman about danger signs of pregnancy and labor. One of the goverment’s program is antenatal class to decrease maternal mortality rate. The purposes of antenatal class are to find the danger signs in pregnancy and labor. This study aims to find out the correlation of mother’s participations in antenatal class and knowledge about danger signs in pregnancy and labor in Denpasar City area. This study applied correlational analytic method with cross- sectional design. The sampling technique used was random cluster sampling. This study was conducted on 1th April untill 1th Mei 2019. The statistical test used in this study was chi-square test. The respondent’s characteristics obtained are: most of the mothers who join the antenatal class have well knowledges of danger signs in pregnancy and labor with a percentage of 71,9%. Chi-square test result preents p value = 0,000. Because of the value of p α (0,05), hence H0 is rejected. So there is correlation of mother’s participations in antenatal class and knowledge about danger signs in pregnancy and labor in Denpasar City area. The sugestion for the next researcher is to find another factors that affect pregnancy woman’s knowledge.